Social Inclusion Predicts Lower Blood Glucose and Low-Density Lipoproteins in Healthy Adults. Issue 8 (3rd August 2017) - Floyd, Kory; Veksler, Alice E.; McEwan, Bree; Hesse, Colin; Boren, Justin P.; Dinsmore, Dana R.; Pavlich, Corey A.
ABSTRACT: Loneliness has been shown to have direct effects on one's personal well-being. Specifically, a greater feeling of loneliness is associated with negative mental health outcomes, negative health behaviors, and an increased likelihood of premature mortality. Using the neuroendocrine hypothesis, we expected social inclusion to predict decreases in both blood glucose levels and low-density lipoproteins (LDLs) and increases in high-density lipoproteins (HDLs). Fifty-two healthy adults provided self-report data for social inclusion and blood samples for hematological tests. Results indicated that higher social inclusion predicted lower levels of blood glucose and LDL, but had no effect on HDL. Implications for theory and practice are discussed.